(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
The transition from manual to automated school inventory management has brought about a significant transformation in the school’s data management processes, particularly in terms of efficiency. This study sought to develop a system that would facilitate the seamless collection of student information by OSAS staff, minimizing human effort and optimizing data accuracy. Employing developmental research approaches, the researchers focused on creating a user-friendly platform to address the specific needs and challenges OSAS personnel face. Essential insights were gathered through documentary analysis of OSAS forms to inform the system’s design and functionality. Utilizing the Waterfall Method, the researchers meticulously crafted the automated inventory system to meet the unique requirements of Union Christian College. The study was conducted within the guidance facilitators and dean’s office of student affairs and services, providing a comprehensive understanding of the system’s impact on daily operations. A detailed examination of the sample data used to test the inventory system was conducted to assess its effectiveness in resolving previous system limitations. To ensure the reliability and efficacy of the inventory system, monitoring mechanisms were implemented to showcase its capabilities and performance under various scenarios. It is strongly recommended that this advanced system be adopted to enhance the school’s current operational framework, enabling staff to carry out tasks efficiently and precisely. By embracing this innovative solution, Union Christian College can elevate its data management practices and streamline administrative processes for improved overall performance.